Factores de riesgo asociados a infecciones del tracto urinario en menores de cinco años en el Hospital Regional de Loreto 2022 - Cruz Ortiz, David Daniel (2025)
Introduction: Urinary tract infections (UTIs) are a very common and significant condition in pediatric patients, with a good clinical prognosis when diagnosed and treated promptly. The present study will focus on the risk factors associated with urinary tract infections in patients under five years old in a hospital in the Amazon. Objective: To determine the risk factors associated with urinary tract infections in children under five years old treated at the Regional Hospital of Loreto in the year 2022. Method: An observational, descriptive, cross-sectional, and retrospective methodological design will be employed. Population: It includes the review of medical records of children under five years old who were treated in various pediatric department services in 2022 after receiving a diagnosis of UTI. Sample: The medical records of children under five years old who meet the inclusion criteria of this study. Results: The processing and analysis of the information will be entered into the IBM SPSS Statistics 29, Microsoft Word, and Microsoft Office Excel 2023 programs, with the results represented in graphs and tables. Conclusion: The present study aims to identify the risk factors associated with urinary tract infections in children under five years old in order to develop prevention strategies for this condition and thus improve the health of the pediatric population.